2017
DOI: 10.1038/s41598-017-09352-5
|View full text |Cite
|
Sign up to set email alerts
|

Responses of renal hemodynamics and tubular functions to acute sodium–glucose cotransporter 2 inhibitor administration in non-diabetic anesthetized rats

Abstract: The aim of this study is to examine the effects of acute administration of luseogliflozin, the sodium–glucose cotransporter 2 (SGLT2) inhibitor, on renal hemodynamics and tubular functions in anesthetized non-diabetic Sprague Dawley (SD) rats and 5/6 nephrectomized (Nx) SD rats. Renal blood flow (RBF), mean arterial pressure (MAP), and heart rate (HR) were continuously measured and urine was collected directly from the left ureter. Intraperitoneal injection of luseogliflozin (0.9 mg kg−1) did not change MAP, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…A direct tubular effect was observed after intraperitoneal injection of luseogliflozin in experimental models without diabetes, regardless of the change in plasma glucose levels and in the absence of hemodynamic renal effects. This is in support of the notion that the mechanism of tubulo-glomerular feedback is unlikely to be triggered [89]. These data provide evidence for an important cross-talk between sympathetic nervous system regulation and SGLT2 inhibition.…”
Section: Data From Clinical and Animal Studies For The Relation Betwesupporting
confidence: 87%
“…A direct tubular effect was observed after intraperitoneal injection of luseogliflozin in experimental models without diabetes, regardless of the change in plasma glucose levels and in the absence of hemodynamic renal effects. This is in support of the notion that the mechanism of tubulo-glomerular feedback is unlikely to be triggered [89]. These data provide evidence for an important cross-talk between sympathetic nervous system regulation and SGLT2 inhibition.…”
Section: Data From Clinical and Animal Studies For The Relation Betwesupporting
confidence: 87%
“…The diuretic actions of SGLT2 inhibitors presumably play an important role in cardioprotection, as shown in the EMPA-REG OUTCOME study and the CANVAS program. SGLT2 inhibitors have acutely caused an increase in urinary sodium excretion in non-diabetic rats [21] and in diabetic rats [22,23]. In type 2 diabetic patients, increased urinary sodium excretion has been observed during the early phase of treatment with canagliflozin [16,18,19] and empagliflozin [24].…”
Section: Diuretic Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…Studies in db/db mice have also shown that hyperglycemia increases kidney volume without enlarging glomeruli and that treatment with SGLT2 inhibitors causes glomerular hypertrophy, glomeruli redistribution, and reduced kidney volume, with no effects on GFR [66]. Similarly, acute administration of luseogliflozin has not changed GFR in non-diabetic rats [21]. However, empagliflozin has resulted in a significant decrease in GFR in Akita mice [67].…”
Section: Diuretic Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…The diuretic actions of SGLT-2 inhibitors presumably play an important role in cardioprotection, as shown in the EMPA-REG OUTCOME study and the CANVAS program. SGLT-2 inhibitors have acutely caused an increase in urinary sodium excretion in non-diabetic [53] and diabetic rats [54,55].Our study showed that addition of dapagli ozin to furosemide actually improved all studied diuresis parameters including urine output, total uid balance as well as uid balance/diuretic dose. In a small randomized, placebocontrolled, double-blind trial, involving 75 subjects with T2DM, dapagli ozin has been shown to reduce plasma volume in a similar way to thiazide diuretics, but dapagli ozin has a more enduring diuretic effect than other diuretics [17].…”
Section: Discussionmentioning
confidence: 56%